2020
DOI: 10.21203/rs.3.rs-136203/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Benson's Relaxation Technique on Occupational Stress Among Nurses Caring for Covid-19 Patients in Sabzevar, Iran

Abstract: Background: Today, nurses face with caring for Covid-19 patients, consider as a new occupational stressor in the nursing profession.Primary Study Objective: To investigate the effect of Benson's relaxation technique (BRT) on occupational stress of nurses exposed to Covid-19 patients.Methods/Design: The present study is a two-group clinical trial with parallel design.Setting: The samples were and randomly allocated into BRT and control groups based on the inclusion and exclusion criteria.Participants: 70 nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…BRT was revealed to have the positive effect of decreasing S&P levels among PUMH. Some studies reported that BRT lowered stress ( Annal & Dhandapani, 2019 ; Borzoee et al, 2020 ; Jourabchi et al, 2020 ; Mohammadi & Parandin, 2019 ; Parmar & Tiwari, 2021 ) and pain levels ( Fitri et al, 2020 ; Mohammadi & Parandin, 2019 ; Molazem et al, 2021 ; Parmar & Tiwari, 2021 ; Titi et al, 2021 ). A SR revealed that BRT provided a beneficial effect by decreasing the anxiety scores of PUMH but it did not reduce depression ( Abu Maloh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRT was revealed to have the positive effect of decreasing S&P levels among PUMH. Some studies reported that BRT lowered stress ( Annal & Dhandapani, 2019 ; Borzoee et al, 2020 ; Jourabchi et al, 2020 ; Mohammadi & Parandin, 2019 ; Parmar & Tiwari, 2021 ) and pain levels ( Fitri et al, 2020 ; Mohammadi & Parandin, 2019 ; Molazem et al, 2021 ; Parmar & Tiwari, 2021 ; Titi et al, 2021 ). A SR revealed that BRT provided a beneficial effect by decreasing the anxiety scores of PUMH but it did not reduce depression ( Abu Maloh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…S&P are clearly endemic among PUMH, and several Randomized Controlled Trials (RCTs) evaluating the efficacy of BRT in various settings have reported a significant decrease in stress levels ( Annal & Dhandapani, 2019 ; Borzoee et al, 2020 ; Jourabchi et al, 2020 ; Mohammadi & Parandin, 2019 ; Parmar & Tiwari, 2021 ) and pain ( Fitri et al, 2020 ; Mohammadi & Parandin, 2019 ; Molazem et al, 2021 ; Parmar & Tiwari, 2021 ; Titi et al, 2021 ). Moreover, an extensive array of bodily and psychological signs and symptoms such as S&P, anxiety, and depression may be affected by BRT ( Elsayed et al, 2019 ).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…In addition, with the increased workload and quarantine measures, this pandemic caused nurses to reduce or cancel their previous leisure activities, such as sports, tourism, and social outings. It changed the quality of life of nurses (45,46). In this regard, promoting work-life balance, supporting self-care activities, and fostering a culture of well-being is very important to address this issue (47-49).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, it seems that the Benson's relaxation technique, as a complementary therapy, supports a comprehensive and extensive self-care program encompassing the physical, emotional, mental, and spiritual aspects of individuals.Working in an environment with high-risk and critically ill patients, occupational stressors such as high workload, stress from infection risk, and many other factors can have many adverse effects and consequences that can affect the quality of life of nurses. Borzoui et al showed that performing relaxation techniques reduces the nurses' anxiety levels after the intervention(55). Additionally, Hassanzadeh et al found that the Benson relaxation technique improved attention, a wide range of physical and mental symptoms, pre-stress symptoms, anxiety, mood, and self-con dence (56).…”
mentioning
confidence: 99%